Johann Natterer and the Amazonian languages - Adelaar, Willem F. H. (2015)
Johann Natterer (1787-1843) was a member of the Austrian scientific expedition that was sent to Brazil in 1817. As a zoologist, Natterer practised taxidermy in situ and provided the Austrian court with a large collection of stuffed animals and ethnographic objects. Less known is his dedication to the collection of linguistic data. After the expedition was called back in 1822, Natterer obtained permission to stay on. He remained in Brazil until 1835 and collected language materials (Sprachproben) of 72 indigenous languages. For many of the languages concerned, Natterer’s hand-written data are either the first or the only records in existence. They are accompanied by ethnographic observations, indicating the original location of groups. In several cases, the speakers of language groups documented by Natterer have since then been removed from their original territories, if their languages were not brought to extinction. After a turbulent history, Natterer’s original language data, which for a long time remained unnoticed, are now kept at the Library of the University of Basel in Switzerland, where they have also been digitalized. Their transcription and publication is being undertaken by the authors of the present article.